Oil palm waste based phthaloyl cellulose: a product of photosynthesis as an electrolyte of photovoltaics - Naceur Abouloula, Cheyma; Rizwan, Muhammad; Selvanathan, Vidhya; Hassan, Aziz; Yahya, Rosiyah; Oueriagli, Amane (Springer, 2019)
Abstract: Waste to wealth extraction of cellulose from oil palm empty fruit bunch was performed. The extracted cellulose was then transformed to an organosoluble derivative, phthaloyl cellulose (PhC). Attachment of the aromatic group was verified by 13 C NMR and FTIR whereas XRD diffractograms endorsed the diminished crystalline nature of the derivative compared to its native form. Ionic conductivity of gels fabricated from PhC incorporated with LiI/I 2 /DMSO recorded a maximum value of 9.73 mS/cm at 13 wt% LiI. As the gel electrolytes were applied in N719 dye based dye-sensitized solar cell, the highest photoconversion efficiency of 3.29% was attained upon addition of 10 wt% LiI. Graphical abstract: [Figure not available: see fulltext.]. © 2019, Springer Nature B.V.